2010
DOI: 10.1089/oli.2009.0206
|View full text |Cite
|
Sign up to set email alerts
|

A High Dose of IMT504, the PyNTTTTGT Prototype Immunostimulatory Oligonucleotide, Does Not Alter Embryonic Development in Rats

Abstract: Synthetic oligodeoxynucleotides (ODNs) are currently being evaluated as vaccine adjuvants for inducing protective immunity. As maternal vaccination is becoming increasingly common, the potential risk of vaccine formulation using ODN adjuvants should be warranted. A recent study performed in mice suggests that exposure to CpG motifs during pregnancy could result (although at very high doses as compared to the ones proposed for human vaccination) in fetal loss and morphological defects. PyNTTTTGT ODNs are immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Furthermore, in preclinical toxicity studies, we demonstrated that IMT504 is a very safe drug (17,23). We are presently validating the effects of IMT504 in NOD mice, a spontaneous model of T1D.…”
Section: (46) Demonstrated Increasedmentioning
confidence: 71%
“…Furthermore, in preclinical toxicity studies, we demonstrated that IMT504 is a very safe drug (17,23). We are presently validating the effects of IMT504 in NOD mice, a spontaneous model of T1D.…”
Section: (46) Demonstrated Increasedmentioning
confidence: 71%
“…Moreover, because IMT504 has good thermal stability, extreme conditions of transport and storage are not necessary. Finally, IMT504 preclinical toxicity studies performed in several animal species, including non-human primates, indicate that IMT504 is a very safe drug with few secondary effects that are well-tolerated and within the therapeutic range of this agent[364,365]. …”
Section: Practical Considerations Regarding the Prospective Clinical mentioning
confidence: 99%
“…Once a lead vaccine candidate is identified, animal models are used to evaluate its safety, immunogenicity, pharmacokinetics and efficacy. Many species, including mouse (Oda et al, 1983;Paoletti et al, 2000;Abram et al, 2003;Chan et al, 2010;Rahman et al, 2010;Monney et al, 2012;Pazos et al, 2012a, b), rat Weisman, 1989, 1990;Zenner et al, 1993;Hernando-Insua et al, 2010;Kim et al, 2011), hamster (Freyre et al, 2012), guinea pig (Harrison et al, 1995;Bourne et al, 2001;Schleiss et al, 2007Schleiss et al, , 2013Schleiss et al, , 2014Leviton et al, 2013), rabbit (Wessels et al, 1990(Wessels et al, , 1993Barrow, 2012;Barrow andAllais, 2013), sheep (Perez-Sancho et al, 2014), pig (Elahi et al, 2006) and non-human primates (Paoletti et al, 2000;Barry et al, 2006;Warfel et al, 2014), have been used.…”
Section: General Guidelinesmentioning
confidence: 99%